Goosebumps presents night of the living dummy II - Ellis, Carol, 1945-; Drew, Rick.; Stine, R. L. (New York : Scholastic, 1996)
When Amy gets a new ventriloquist dummy, strange things begin to happen.
"A Parachute Press book"--T.p. verso.
2.2.
2.2
5-8
Keywords: Horror stories; Ventriloquism -- Fiction; Horror fiction; Ventriloquism -- Fiction